2018
DOI: 10.4149/bll_2018_016
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of high-dose human albumin against traumatic spinal cord injury in rats

Abstract: BACKGROUND AND OBJECTIVES: Human serum albumin (HA) is a unique multifunctional protein with neuroprotective properties. We aimed to delineate the mechanisms of HA-induced neuroprotection, supresses infl ammatory response and lipid peroxidation after spinal cord injury (SCI). METHODS AND STUDY DESIGN: Adult female Wistar rats weighing 210-250 g were used for the study. The rats were randomly and blindly allocated into fi ve groups. The one-way analysis of variance (ANOVA) for parametric data and Shapiro-Wilk t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Albumin's neuroprotective action has been reported in vitro in preventing neurotoxicity in hippocampal slice cultures (Dani et al, 2019) and DNA damage (Baltanas et al, 2009), zinc toxicity (Lin et al, 2005), oxidative stress (Gum et al, 2004), and intracellular calcium overload (Gallego-Sandin et al, 2005) in cultured neurons. Its beneficial effect has also been documented in vivo in rat (Park et al, 2017;Yildirim et al, 2018) and in humans (Palesch et al, 2006;Suarez et al, 2012). Interestingly, in a transgenic mouse model of Alzheimer's disease (Ezra et al, 2016), HSA-treated mice showed increased myelin integrity and myelin basic protein (MBP) protein level.…”
Section: Discussionmentioning
confidence: 97%
“…Albumin's neuroprotective action has been reported in vitro in preventing neurotoxicity in hippocampal slice cultures (Dani et al, 2019) and DNA damage (Baltanas et al, 2009), zinc toxicity (Lin et al, 2005), oxidative stress (Gum et al, 2004), and intracellular calcium overload (Gallego-Sandin et al, 2005) in cultured neurons. Its beneficial effect has also been documented in vivo in rat (Park et al, 2017;Yildirim et al, 2018) and in humans (Palesch et al, 2006;Suarez et al, 2012). Interestingly, in a transgenic mouse model of Alzheimer's disease (Ezra et al, 2016), HSA-treated mice showed increased myelin integrity and myelin basic protein (MBP) protein level.…”
Section: Discussionmentioning
confidence: 97%
“… 10 , 19 , 20 According to previous studies, albumin may exert neuroprotective function via its anti-inflammatory activity, antioxidant characteristics, inhibiting endothelial apoptosis, and regulating microvascular permeability. 21–23 Another theory is that low albumin in time of acute stroke could illustrate the role albumin’s concentration plays during inflammation states as a negative acute phase reactant. 24 Negative regulation of the albumin synthesis may be controlled via interleukin (IL-6 and tumor necrosis factor, which are seen in increased concentrations during states of acute inflammation, such as acute stroke.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] This is why current studies on SCI treatment focus on secondary injury, and the antioxidant effects of neuroprotective agents play an important role in this area. [22][23][24] The negative results obtained from many clinical and experimental studies have shown that there is an urgent need for an effective, non-toxic neuroprotective agent with a low side effect profile in the treatment of SCI.…”
Section: Discussionmentioning
confidence: 99%